Recombinase-aided amplification assay for rapid detection of imipenem-resistant Pseudomonas aeruginosa and rifampin-resistant Pseudomonas aeruginosa - Zhou, Yao; Shi, Ruiqing; Mu, Liang; Tian, Linlin; Zhou, Mengshan; Lyu, Wenhan; Chen, Yaodong (Frontiers in Cellular and Infection Microbiology, 2024)
The indiscriminate use of antibiotics has resulted in a growing resistance to drugs in Pseudomonas aeruginosa. The identification of antibiotic resistance genes holds considerable clinical significance for prompt diagnosis. In this study, we established and optimized a Recombinase-Aided Amplification (RAA) assay to detect two genes associated with drug resistance, oprD and arr, in 101 clinically collected P. aeruginosa isolates. Through screening for the detection or absence of oprD and arr, the results showed that there were 52 Imipenem-resistant P. aeruginosa (IRPA) strains and 23 Rifampin-resistant P. aeruginosa (RRPA) strains. This method demonstrated excellent detection performance even when the sample concentration is 10 copies/μL at isothermal conditions and the results could be obtained within 20 minutes. The detection results were in accordance with the results of conventional PCR and Real-time PCR. The detection outcomes of the arr gene were consistently with the resistance spectrum. However, the antimicrobial susceptibility results revealed that 65 strains were resistant to imipenem, while 49 strains sensitive to imipenem with oprD were identified. This discrepancy could be attributed to genetic mutations. In summary, the RAA has higher sensitivity, shorter time, and lower-cost instrument requirements than traditional detection methods. In addition, to analyze the epidemiological characteristics of the aforementioned drug-resistant strains, we conducted Multilocus Sequence Typing (MLST), virulence gene, and antimicrobial susceptibility testing. MLST analysis showed a strong correlation between the sequence types ST-1639, ST-639, ST-184 and IRPA, while ST-261 was the main subtype of RRPA. It was observed that these drug-resistant strains all possess five or more virulence genes, among which exoS and exoU do not coexist, and they are all multidrug-resistant strains. The non-coexistence of exoU and exoS in P.aeruginosa is related to various factors including bacterial regulatory mechanisms and pathogenic mechanisms. This indicates that the relationship between the presence of virulence genes and the severity of patient infection is worthy of attention. In conclusion, we have developed a rapid and efficient RAA (Recombinase-Aided Amplification) detection method that offers significant advantages in terms of speed, simplicity, and cost-effectiveness (especially in time and equipment aspect). This novel approach is designed to meet the demands of clinical diagnostics.